2016
DOI: 10.3390/nano6100189
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Silver Nanoparticle and Chitin-Nanofiber Sheet Composites Caused by Oxidative Stress

Abstract: Size-controlled spherical silver nanoparticles (<10 nm) and chitin-nanofiber sheet composites (Ag NPs/CNFS) have previously been reported to have strong antimicrobial activity in vitro. Although Ag NPs/CNFS have strong antimicrobial activity, their cytotoxicity has not been investigated. This study was performed to evaluate the effects of Ag NPs/CNFS on cytotoxicity for fibroblasts in vitro and healing delay of wound repair in vivo, focused on oxidative stress. Cytotoxic activities of Ag NPs/CNFS were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…For further histological observation, 8-OHdG immunohistochemical staining of skin sections at 24 h after wound creation was performed to measure the 8-OHdG–positive spots. The 8-OHdG staining indicates the hyperoxidation state of the nucleic acids, allowing the anti-oxidative effect to be evaluated [ 10 , 25 ]. We found 8-OHdG–positive staining at the wound surface in both the X-irradiated FGF-2&LMWH/P NPs and control groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For further histological observation, 8-OHdG immunohistochemical staining of skin sections at 24 h after wound creation was performed to measure the 8-OHdG–positive spots. The 8-OHdG staining indicates the hyperoxidation state of the nucleic acids, allowing the anti-oxidative effect to be evaluated [ 10 , 25 ]. We found 8-OHdG–positive staining at the wound surface in both the X-irradiated FGF-2&LMWH/P NPs and control groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…of wound healing and with the higher concentrations required for disinfectant activity, compared to BiSCaO, NaClO, and HClO (Kinoda et al, 2016;McCauley et al, 1989;Wiegand et al, 2015) . Therefore, a topical disinfectant that can decrease the bacterial bioburden of chronic wounds without inhibiting the wound healing process is a therapeutic imperative.…”
Section: Fig 3 Disinfection Efficacy For Removing Microbes From Skimentioning
confidence: 99%
“…to the cellular components for wound healing (Wiegand et al, 2015) , since higher concentrations are required for bactericidal activity (Kinoda et al, 2016;McCauley et al, 1989) . This has led to the current use of various disinfectants such as silver nanoparticles (Ishihara et al, 2015;Nguyen et al, 2014;Mori et al, 2011) , bio-shell calcium oxides (BiSCaO) powder, hypochlorous acid (HClO) , and sodium hypochlorite (NaClO) , based on their bactericidal properties with relatively low concentrations.…”
mentioning
confidence: 99%
“…81 Many reports have shown that metallic NPs can significantly enhance the formation of ROS in skin cells. 8,82,83 Increased NO/ NO 2 and decreased GPx in fibroblasts and HaCaT cells have been observed after exposure to metallic NPs, indicating that NPs caused inflammatory responses and metabolic changes. Additionally, NPs affected the gene expression of SOD and GPx.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Meanwhile, decreased GPx led to a reduction in toxic peroxides in cells. 16,68,82 Similarly, an in vitro study showed that oxidative stress was the key cause of mitochondrial membrane damage, cell-cycle arrest, and DNA damage after mouse-skin fibroblast cells had been exposed to MoNPs. 84 The secondary effect of ROS caused the activation of cell-death-mediated signaling via NFκB.…”
Section: Oxidative Stressmentioning
confidence: 99%